Anticancer effect of deuterium oxide on a bladder cancer cell related to bcl-2 and bax - Bahk, Jong Yoon; Lee, Jeong-Hee; Chung, Hong Suk; Lee, Hae Young; Chung, Bong Chul; Park, Moon Seok; Min, Seung Ki; Kim, Myeong Ok (ELSEVIER SCIENCE INC, 2007)
To evaluate the potentiality, as a drug for an intravesical instillation after a transurethral resection of a bladder tumor, we studied the anticancer effects of deuterium oxide (D2O) related to bcl-2 and bax. Bladder cancer cell T-24 was used and culture media were prepared with H2O and D2O at different concentrations (D2O V/V), 0 (control), 75, and 100 %. Cells were exposed to each D2O for 2, 2.5, 3, and 3.5 h. The antiproliferative effects were measured by a quantitative colorimetric assay (MTT assay) and a hemocytometer. Invasion study was implemented with a modified reconstituted basement membrane after an exposure to D2O. Immunohistochemical staining and Western blot analysis for bcl-2 and bax were implemented to evaluate the relation between D2O and apoptosis. Marked cytoreduction was observed at an exposure to both 75 and 100 % of D2O. The cellular proliferation in 75 % D2O was 68.95, 46.77, 24.65, and 14.41 % when compared to the control at an exposure time of 2, 2.5, 3, and 3.5 h, respectively. The comparative ratios in 100 % were 37.93, 4.30, 1.00, and 0.18% at each exposure group. An invasion of the D2O exposed cells into the reconstituted basement membrane did not occur. Morphologic cellular findings suggested an apoptosis. The bcl-2 and bax proteins were noted from most cells regardless of an exposure to D2O. The expressions of the bcl-2 were decreased with an increased exposure time in both the 75 and 100 % D2O. The expressions of the bax were increased with an increased exposure time for both concentrations. D2O has high antiproliferative, and anti-invasive effects at 75 and 100 % D2O with an exposure time longer than 2.5 h. We concluded that the mechanism of the antiproliferative effect of the D2O would be mediated by an apoptosis. And the cytotoxic results related to D2O show the potential for an application as an agent for a post TUR-BT intravesical instillation in a superficial bladder cancer.
Keywords: HEAVY-WATER; CIGARETTE-SMOKING; MESSENGER-RNA; APOPTOSIS; TUMOR; IMPLANTATION; EXPRESSION; MECHANISM; CISPLATIN